Hand, foot, and mouth disease in children: forecasting of future research direction using bibliometric analysis - Tan, Santi; Tjandrawinata, Raymond Rubianto (Faculty of Pharmacy, Universitas Pancasila, 2024)
Since 1997, hand, foot, and mouth disease (HFMD) has become a common health problem in Southeast Asia. Various types of research have been conducted and published to handle HFMD. However, until now, many children, especially in the Asia-Pacific region, including Indonesia, still have HFMD-causing enterovirus (EV) infection. By conducting a bibliometric analysis of the literature published over the last 27 years (1997–2024), the direction of HFMD research in children can be predicted, thus research areas that have the potential and still need to be developed for future better HFMD treatment can be known. The important HFMD research topics predicted to continue to develop were identified through keyword analysis, which was subsequently mapped using a network approach. Based on this study, it can be concluded that HFMD research is predicted to lead to the development of synbiotic supplements, which can reduce HFMD severity, especially in children, by utilizing a genome-wide association study (GWAS) and machine learning.